Errors and Difficulties Encountered by English for Specific Purposes Learners in using Relative pronouns - Dr. Edhah Numan Khazaal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to identify the ESP learners' errors and difficulties in using relative pronouns (who, whom, which, whose and that), and to discover the reason for making errors. The researcher has applied the quantitative analytical method to conduct the study. The sample of the study was 50 students out of 90 students’ population, at Al-Nahrain University /College of Political Sciences for the academic year 2018-2019. Awritten test and student interview were used for data analysis. The written test consisted of three different questions, each question consist of 10 items; 10 items of fill in the blanks and 10 sentence combination test items, and 10 correcting sentence errors, so the total items are 30.Based on the data analysis. Most of the ESP students had problems in using the wrong relative pronoun, especially with "whom" and "that". The researcher recommends that students should enlarge their knowledge in the grammar field, and they should practice well how to use the relative pronouns in sentences. Moreover, teachers must apply modern strategies and techniques in teaching this activity.